Fachkommunikation im Bereich der Zahnmedizin am Beispiel der deutschen und polnischen Webseiten von Zahnkliniken - Patrycja Czakon (Linguistische Treffen in Wrocław, 2025)
Specialist communication concerns many areas, e.g. technology, medicine, or construction. It accompanies us not only in our working lives but also in our daily lives. An important aspect of technical communication between experts and laypeople is to convey the message briefly and simply in order to achieve the goal of comprehensibility. Specialized language plays a very important role in technical communication. They are the basis of communication and enable understanding in a particular specialized field. Specialist communication often takes place between an expert and an expert who can easily understand the specialist vocabulary of the field in which they specialize. In the case of communication between an expert and a layperson, specialized communication must be based on the fact that the vocabulary used by the expert can also be understood by a person who is not an expert in the field in question. The article analyses specialist communication in the field of dentistry on the example of German and Polish dental clinic websites. They were investigated according to various criteria, e.g. the design of the website and the number of images, the number of specific tabs, and the use of technical language. Each criterion aims to highlight the differences and similarities that emerge from analyzing the German and Polish websites.